The leadership role of creative guilds and trade union to sustain the Malaysia’s creative industry - Yasin, Megat Al-imran; Mohamad Isa, Siti Fariza (Majmuah Enterprise, 2024)
The existence of the Dasar Industri Kreatif Negara (DIKN) in 2009, with the mission to govern the creative and cultural industry systematically, would change the landscape of the practice and way forward of the creative practitioners, with little production of content in the creative industry, but with so many establishments of creative guilds that are acknowledged by the National Film Development Corporation Malaysia (FINAS) and not to mention the establishments of Trade Unions by the Department of Human resource. This has perplexed the creative industry players by the distinctive functions and features of a guild and union, for they know both parties were established to protect them. This study’s objective is to understand the effects of leadership roles in trade unions and creative guilds that hold the potential to elevate the creative industry's well-being. This study will qualitatively interview two (2) leaders of Kesatuan Sekerja Kakitangan Sistem Televisyen Malaysia Berhad (STMB) and Akademi PROFIMA. The impact of this study is expected to provide in-depth literacy of the leadership roles of trade unions and creative guilds that would provide service and protection to the creative industry players.